(untitled) (Bangladesh Journal of Plant Taxonomy, 2010)
Not available. Keywords: Rediscovery; Appendicula cornuta Bl.; Generic record; Meghalaya; India. DOI: 10.3329/bjpt.v17i2.6700 Bangladesh J. Plant Taxon. 17(2): 199-202, 2010 (December)